Political Modernity and Social Theory : Origins, Development and Alternatives - Jose Maur¡cio Domingues (Routledge, 2024)
Modern liberal democracy and authoritarian collectivism have known diverse political regimes; autocratic, oligarchic or democratic, they each consist of a mixed, partly oligarchic regime in which plebeian politics are subordinated. With authoritarian collectivism's defeat, a return to modernity has produced one more hybrid configuration.An in-depth investigation of political modernity and how it is differentiated from other forms of society, this book researches its origins and trajectory as a specific dimension of modern civilisation – articulating a renewed critical theory through an analysis of rights and law, politics, state and autonomy, social reproduction, crisis and political change.Examining these diverse aspects, Political Modernity and Social Theory proposes an encompassing and far-reaching approach spanning past and present – stressing radical plebeian democracy and maintaining a strong opening to the future and to possible alternatives to modernity.The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution (CC-BY) 4.0 license.